2006
DOI: 10.1213/01.ane.0000194292.81614.c6
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Versus General Anesthesia for Orthopedic Surgery: Anesthesia Drug and Supply Costs

Abstract: Total hip or knee replacement surgeries are common orthopedic interventions that can be performed with spinal anesthesia (SA) or general anesthesia (GA). No study has investigated the economic aspects associated with the two anesthetic techniques for this common surgery. We randomized 40 patients to receive either SA or GA and analyzed the drug and supply costs for anesthesia und recovery. Anesthesia-related times, hemodynamic variables, and pain scores were also recorded. Total costs per case without personne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 14 publications
2
75
0
2
Order By: Relevance
“…In contrast to perceived delays total hip replacement surgery operating times were significantly reduced in patients receiving regional anesthesia [12] . Some studies argue that spinal anesthesia is associated with a benefit reflected in significant cost-reduction both in anesthesia times and recovery compared to general anesthesia in total hip or knee replacement operations [57] . When studying population data, results suggest a lower incidence of increased cost in neuraxial patients combined with a lower risk for prolonged length of stay [6] .…”
Section: Economic Outcomesmentioning
confidence: 99%
“…In contrast to perceived delays total hip replacement surgery operating times were significantly reduced in patients receiving regional anesthesia [12] . Some studies argue that spinal anesthesia is associated with a benefit reflected in significant cost-reduction both in anesthesia times and recovery compared to general anesthesia in total hip or knee replacement operations [57] . When studying population data, results suggest a lower incidence of increased cost in neuraxial patients combined with a lower risk for prolonged length of stay [6] .…”
Section: Economic Outcomesmentioning
confidence: 99%
“…If both methods are equally effective and yield similar outcomes, then the least expensive is rationally preferable. For knee and hip arthroplasty, one previous study reported that the total cost per case (without personnel costs) was twice as much for general compared with spinal anaesthesia [15]. The main aim of this study was to assess if this was also the case when personnel costs were included for hip fracture repair.…”
mentioning
confidence: 98%
“…After conducting a small randomized controlled trial to investigate the costs associated with GA and spinal anesthesia for elective hip or knee replacement, Gonano et al found that spinal anesthesia is more cost-effective than GA as it is associated with lower fixed and variable costs. 28 We investigated the total hospital treatment costs for primary total hip or knee replacements performed in Taiwan from 1997 to 2010. As there was a significant difference in the costs of different anesthetic techniques we investigated the hospital treatment costs with and without anesthesia-related expenses.…”
Section: Discussionmentioning
confidence: 99%